Les échantillons de médicaments influencent-ils les prescriptions des résidents? Un essai randomisé - Gauthier, Josianne; Doyon, Sophie; Marquis, Christopher; Perreault, Mélissa; Lebel, Denis (Pharmactuel, 2015)
-